2011
DOI: 10.1080/19345747.2010.523513
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Experiment of a Cognitive Strategies Approach to Text-Based Analytical Writing for Mainstreamed Latino English Language Learners in Grades 6 to 12

Abstract: This study reports year 1 findings from a multi-site cluster randomized controlled trial of a cognitive strategies approach to teaching text-based analytical writing for mainstreamed Latino English Language learners (ELLs) in 9 middle schools and 6 high schools. 103 English teachers were stratified by school and grade and then randomly assigned to the Pathway Project professional development intervention or control group. The Pathway Project trains teachers to use a pretest on-demand writing assessment to impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 34 publications
1
44
0
Order By: Relevance
“…Summary statistics were obtained directly from the researchers in other instances (e.g., J.S. Kim et al., ; Olson et al., ). Several quasi‐experiments (e.g., Stevens, ; Stevens et al., ) had pretest measures that were conceptually similar but not identical to the corresponding posttest measures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Summary statistics were obtained directly from the researchers in other instances (e.g., J.S. Kim et al., ; Olson et al., ). Several quasi‐experiments (e.g., Stevens, ; Stevens et al., ) had pretest measures that were conceptually similar but not identical to the corresponding posttest measures.…”
Section: Methodsmentioning
confidence: 99%
“…Five studies (J.S. Kim et al, ; Murphy & Appel, ; Olson & Land, ; Olson, Matuchniak, Chung, Stumpf, & Farkas, ; Stevens, ) had sample sizes that exceeded the outlier status of N = 2,125. The standard errors for reading and writing ESs were adjusted accordingly.…”
Section: Methodsmentioning
confidence: 99%
“…Although a method for conducting cost-effectiveness analysis in education has been available for many years using straightforward cost accounting methods based upon opportunity costs (see Chambers & Parrish, 1994a, 1994bLevin, 1975), its application has been limited to only a few educational interventions such as teacher selection (e.g., Levin, 1970); computer-assisted instruction, smaller class sizes, longer school days, and cross-age tutoring (e.g., Levin, Glass, & Meister, 1987); adolescent literacy programs (e.g., Kim et al 2011;Levin, Catlin, & Elson, 2007); and dropout prevention (e.g., Hollands et al, 2014).…”
mentioning
confidence: 99%
“…For example, the Pathway Project, a professional development program designed and facilitated by the University of California Irvine Writing Project, works with teachers to support English Language Learners in mainstream classrooms as they improve their capacity to write academic essays. Researchers, who conducted a randomized trial, found that students who were in classrooms with trained Pathway Project teachers improved both their writing scores on an assessment completed for the research and their scores on state English Language Arts tests (Kim et al, 2011).…”
Section: National Writing Projectmentioning
confidence: 99%
“…Researchers continue to find positive relationships between Writing Project professional development initiatives and improved teacher practice and student outcomes (Kim et al, 2011;Stokes, 2011). For example, the Pathway Project, a professional development program designed and facilitated by the University of California Irvine Writing Project, works with teachers to support English Language Learners in mainstream classrooms as they improve their capacity to write academic essays.…”
Section: National Writing Projectmentioning
confidence: 99%